High‐selectivity wideband balanced bandpass filters using symmetrical multi‐mode resonators. Issue 12 (1st September 2013) - Feng, Wenjie; Che, Wenquan; Gu, Liming; Xue, Quan
Abstract : Two novel high‐selectivity wideband balanced bandpass filters using symmetrical multi‐mode resonators are presented. The proposed novel multi‐mode resonator is used to realise a six‐order wide passband in the differential mode. In addition, wide stopbands with insertion loss greater than 15 and 20 dB for the commode mode (0–18.5 GHz, 0–19 GHz) can also be achieved by the multi‐mode resonators. The even/odd‐modes of the symmetrical multi‐mode resonators can be adjusted by changing the characteristic impedance of the shorted/open stubs. Two planar wideband balanced filters with 3 dB fractional bandwidths of 67.6 and 63.7% are designed and fabricated. The theoretical and measured results are in good agreement and show good in‐band filtering performances and high selectivity.